Mycobacterial biomaterials and resources for researchers. Issue 4 (19th April 2018) - Hazbón, Manzour Hernando; Rigouts, Leen; Schito, Marco; Ezewudo, Matthew; Kudo, Takuji; Itoh, Takashi; Ohkuma, Moriya; Kiss, Katalin; Wu, Linhuan; Ma, Juncai; Hamada, Moriyuki; Strong, Michael; et al.
Abstract: There are many resources available to mycobacterial researchers, including culture collections around the world that distribute biomaterials to the general scientific community, genomic and clinical databases, and powerful bioinformatics tools. However, many of these resources may be unknown to the research community. This review article aims to summarize and publicize many of these resources, thus strengthening the quality and reproducibility of mycobacterial research by providing the scientific community access to authenticated and quality-controlled biomaterials and a wealth of information, analytical tools and research opportunities. Abstract : This review aims to raise awareness among mycobacterial researchers of the many global resources available, including culture collections distributing mycobacterial biomaterials as well as other valuable resources such as databases and computational/bioinformatics tools.